Pengaruh Beberapa Jenis Pupuk Kandang Terhadap Kualitas Bokashi - Maria Erviana Kusuma (JURNAL ILMU HEWANI TROPIKA (JOURNAL OF TROPICAL ANIMAL SCIENCE), 2012)
The environmental friendly ranch development and base on the local resources represent the strategic step in realizing the quality and amount of ranch product. Exploiting of livestock waste as organic manure in agriculture crop longer progressively expand. One of the way of exploiting livestock waste dirt with the processing bokashi. This experiment was conducted to know the manure to quality bokashi. This experiment using Complete Random Device with the single treatment of kind of manure ( P), that are manure from cow ( p1), chicken ( p2), goat ( p3) and pig ( p4). The result of this experiment are some kind of manure have an effect on to quality bokashi among others content of element of hara P and K while from colour, smell and tekstur is not different from colour, smell and tekstur materials. All type of manure have not effect on to content of N and C/N ratio bokashi. Bokashi from pig manure have the highest content of P, and bokashi from goat manure have the highest K from the other bokashi.